2014
DOI: 10.2306/scienceasia1513-1874.2014.40.060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaCl and sugar on physicochemical properties of flaxseed polysaccharide-potato starch complexes

Abstract: To investigate the effect of salt and sugar on the physicochemical properties of flaxseed polysaccharidepotato starch (FG-PS) complexes we measured pasting, gelling, swelling properties, and freeze-thaw stability by methods of rapid viscosity analysis, texture analysis, centrifugation, and freeze-thaw storage, respectively. In the presence of NaCl, the pasting temperature, peak viscosity, final viscosity, breakdown value, and swelling power of FG-PS complexes increased as the NaCl level increased. The hardness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
7
20
0
Order By: Relevance
“…The SB value indicates the retrogradation tendency of the pasted starch, due to the aggregation of amylose during cooling (Varela et al, 2016;Wu et al, 2016). The increase in PT value of the starch with the addition of hydrocolloids was in accordance with the previous studies (Chen, Wang, Leng, Zhao, & Zhao, 2014;Krystyjan, Ciesielski, Khachatryan, Sikora, & Tomasik, 2015;. The high SB value indicated that PS exhibited a high tendency to retrograde.…”
Section: Pasting Propertiessupporting
confidence: 86%
See 1 more Smart Citation
“…The SB value indicates the retrogradation tendency of the pasted starch, due to the aggregation of amylose during cooling (Varela et al, 2016;Wu et al, 2016). The increase in PT value of the starch with the addition of hydrocolloids was in accordance with the previous studies (Chen, Wang, Leng, Zhao, & Zhao, 2014;Krystyjan, Ciesielski, Khachatryan, Sikora, & Tomasik, 2015;. The high SB value indicated that PS exhibited a high tendency to retrograde.…”
Section: Pasting Propertiessupporting
confidence: 86%
“…Li, Wang, Chen, Liu et al (2017) reported that the presence of AG promoted the PT value of cornstarch. Moreover, the increased PT value for PS may be attributed to the strong electrostatic repulsions between the phosphate group of PS and the carboxyl group of AG (Chen, Wang, et al, 2014). Chen, Wang et al (2014) reported that the presence of flaxseed polysaccharide promoted the PT value of PS.…”
Section: Pasting Propertiesmentioning
confidence: 99%
“…NaCl impeded the retrogradation of rich starch via decreased water mobility in the starchwater system, resulting in the lower association of the starch chains. The hardness of the potato starch gel stored at 4 C for 24 h was reported to be decreased with increased NaCl (Chen, Wang, Leng, Zhao, & Zhao, 2014) because the electrostatic repulsion between the phosphate group in the potato starch and the salt. Moreover, due to the less compact structure of noodle with NaCl, some starch molecules dissolved in boiling water as shown in the high cooking loss, resulting in less solids being left in the cooked rice noodle.…”
Section: Samplementioning
confidence: 99%
“…Sodium chloride added to the dissolution medium will form Na + and Cl -ions, which will decrease the expanding ability of cross-linked amylose. The presence of electrostatic interactions between amylose and sodium chloride and the competition between amylose and sodium chloride in binding water molecules causes a decrease in the expanding ability of crosslinked amylose [17]. According to Fig.…”
Section: Drug Release (Dissolution) Testmentioning
confidence: 98%
“…1, the percentage of the released drug is in the range of 45-75%, which according to the Banakar rule, means it can be used as a 16-hrs sustained-release tablet. This is due to the influence of electrolytes in the medium, which leads to a decrease in its ability to inflate amylose cross-link excipients [17]. Figs.…”
Section: Drug Release (Dissolution) Testmentioning
confidence: 99%